Tourist experience elements structure characteristics analysis of Xixi National Wetland Park based on web text - Jing, Fengrui; Sun, Hu; Long, Dongping (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2017)
There are few researches on tourism experience elements structure analysis based on web text. We chose Xixi National Wetland Park as empirical object and selected tourists' comments on Ctrip as text data sources. Based on the coded tourism experience elements and the evaluated grades of the comment text with the method of textual analysis, we established tourism experience element structure and tourism experience evaluation data sets. In detail, we analyzed the structure characteristics by means of social network analysis (SNA) and IPA analysis. The SNA results showed that the structure had a high degree of coordination. The wetland natural landscape was the most core element of perception. The structure was divided into two statistical significant subgroups and two statistical in significant subgroups. The IPA results showed that the performance scores of most elements were high, which showed that tourists had a high evaluation on Xixi national wetland park. The importance scores of elements were remarkable